Facilitating Adaptive Emotion Processing and Somatic Reappraisal via Sustained Mindful Interoceptive Attention - Price, Cynthia J.; Weng, Helen Y. (Frontiers in Psychology, 2021)
Emotions are by nature embodied, as the brain has evolved to quickly assess the emotional significance of stimuli and output signals to the body’s viscera and periphery to aid adaptive responses. Emotions involve both implicit bodily and explicit narrative processes, and patients may experience transdiagnostic distress when bodily signals are not attended to and holistically integrated with explicit narratives about experience. Similarly, therapists may be trained in more implicit body-based approaches (i.e., massage/bodywork, physical and occupational therapy, nursing/medicine) or more explicit narrative-based approaches (i.e., psychotherapy), and may lack training in skills that integrate both levels of emotion processing to aid healing and growth. To address these gaps, we propose a framework where the bridge between implicit bodily sensations and explicit narratives lies in cultivating mindful awareness of bodily sensations associated with emotions. This process brings subjective awareness to notice inner body experience (or interoceptive awareness) that is often outside of conscious awareness, so that it may be understood and re-integrated in more adaptive ways, which we call somatic reappraisal. Using clinical theory and example vignettes, we present mindful interoceptive awareness for adaptive emotion processing as a framework to cultivate and enhance somatic reappraisal. Mindful interoceptive awareness brings more focused and sustained attention to inner body experience; likewise, internal sensations associated with emotions become more granular, vivid, and can shift in ways that facilitate somatic reappraisal. Learning to sustain interoceptive awareness when engaged with mindfulness qualities of nonjudgment and compassion promotes an experience where new associations between emotions, meanings, and memories can be made that generate insights that are holistic and integrative. A clinical vignette is used in this paper to provide examples of this approach in psychotherapy. An example script for use in mindfulness groups is included, and resources are suggested for clinicians to gain more experience. Mindful interoceptive awareness for adaptive emotion processing is a clinical process that can be learned and applied by a range of clinicians to treat mental and physical health conditions that may benefit greater embodied awareness.